Establishment and inheritance of epigenetic transcriptional memory - Sump, Bethany; Brickner, Jason (Frontiers in Molecular Biosciences, 2022)
For certain inducible genes, the rate and molecular mechanism of transcriptional activation depends on the prior experiences of the cell. This phenomenon, called epigenetic transcriptional memory, accelerates reactivation and requires both changes in chromatin structure and recruitment of poised RNA Polymerase II (RNAPII) to the promoter. Forms of epigenetic transcriptional memory have been identified in S. cerevisiae, D. melanogaster, C. elegans, and mammals. A well-characterized model of memory is found in budding yeast where memory of inositol starvation involves a positive feedback loop between gene-and condition-specific transcription factors, which mediate an interaction with the nuclear pore complex and a characteristic histone modification: histone H3 lysine 4 dimethylation (H3K4me2). This histone modification permits recruitment of a memory-specific pre-initiation complex, poising RNAPII at the promoter. During memory, H3K4me2 is essential for recruitment of RNAPII and faster reactivation, but RNAPII is not required for H3K4me2. Unlike the RNAPII-dependent H3K4me2 associated with active transcription, RNAPII-independent H3K4me2 requires Nup100, SET3C, the Leo1 subunit of the Paf1 complex and can be inherited through multiple cell cycles upon disrupting the interaction with the NPC. The H3K4 methyltransferase (COMPASS) physically interacts with the potential reader (SET3C), suggesting a molecular mechanism for the spreading and re-incorporation of H3K4me2 following DNA replication. Thus, epigenetic transcriptional memory is a conserved adaptation that utilizes a heritable chromatin state, allowing cells and organisms to alter their gene expression programs in response to recent experiences over intermediate time scales.